Analysis Of Multi Item Raw Material Inventory Supply Using The Economic Order Quantity Method - Anidah, Anidah; Nasution, Hamidah; Widyasari, Rina (ZERO: Jurnal Sains, Matematika dan Terapan, 2020)
Raw material inventory control has a positive impact to support the smooth production process in increasing company profits, one of which is the production of chicken feed at PT. Mabar Feed Indonesia. This study aims to determine the economic order quantity of multi-item chicken feed raw material inventory, and to compare the control of multi-item chicken feed raw material inventory used by companies with the control of multi item chicken feed inventory using the EOQ method. In this study to analyze the data first used the normality test data with the Lilliefors test where the data is normally distributed. The total cost of raw material inventory according to PT Mabar Feed Indonesia is Rp.   the cost is greater than the cost obtained by the EOQ method, which is Rp.   and savings can be made of  Rp.   of the cost of raw material inventory according to PT. Mabar Feed Indonesia.